The relationship between impostor phenomenon and emotional exhaustion among Chinese nurses: the mediating role of bi-directional work-family conflict - Yuan Li; Yuan Li; Yuan Li; Fangxinrui Qiu; Biru Luo; Biru Luo; Yanling Hu; Yanling Hu; Yanling Hu; Jie Li; Ying Xin Li; Ying Xin Li; et al. (Frontiers in Public Health)
AimsThe study aims to explore the relationship between impostor phenomenon and emotional exhaustion among nurses and to examine the potential mediating role of bi-directional work–family conflict.MethodsA cross-sectional survey using convenience sampling was conducted from January to April 2023, involving 4,088 Chinese nurses. Of those, 3,977 nurses across 43 public hospitals completed the web-based survey that included a sociodemographic information questionnaire, the short Clance Impostor Phenomenon Scale, the Bi-directional Scale of Work–Family Conflict, and the Emotional Exhaustion Scale. SPSS with Hayes’s PROCESS v4.2 Macro was employed to examine the mediation model using bootstrap techniques.ResultsAfter controlling for confounding factors, impostor phenomenon was found to have a direct positive effect on emotional exhaustion (𝛽 = 0.134, 95% CI [0.122 to 0.145]); the two dimensions of work–family conflict, work interfering with family (𝛽 = 0.099, 95% CI [0.090 to 0.109]) and family interfering with work (𝛽 = 0.017, 95% CI [0.012 to 0.022]), served as parallel mediators in the relationship between impostor phenomenon and emotional exhaustion. Compared to family interfering with work, impostor phenomenon had a greater influence on emotional exhaustion through the mediation of work interfering with family, with a difference in the mediating effects of 0.082 (95% CI [0.073 to 0.096]). (The symbol β denotes the regression coefficient, estimated through mediation analysis using a bias-corrected bootstrapping procedure. CI represents the confidence interval for the specified parameter).ConclusionThis study reveals that impostor phenomenon not only directly affects emotional exhaustion but also exerts parallel mediation effects through bi-directional work–family conflict, with work interfering with family exerting a stronger mediating effect than family interfering with work. The findings elucidate the complex interplay between impostor phenomenon, an intrapersonal psychological factor, and work–family conflict, an interpersonal stressor, in contributing to emotional exhaustion among Chinese nurses, providing valuable insights to guide efforts aimed at safeguarding nurses’ mental health and well-being.